Development and Evaluation of a Molecular Viability Assay for Pneumocystis carinii - Maher, Nancy (American Society for Microbiology, 2000)
Despite recent declines in incidence, Pneumocystis carinii pneumonia (PCP) remains the most commonly occurring opportunistic illness among persons with AIDS in the United States. While P. carinii DNA has been detected in patient respiratory specimens and in air samples collected from various indoor environments housing PCP patients, the viability of these organisms is unknown. For this reason, we have developed and evaluated a molecular viability assay for P. carinii. This method is based upon the detection of P. carinii mRNA by a reverse transcription-PCR that employs specific primers from a member of the heat shock protein 70 family. Under optimal assay conditions, these primers were capable of detecting as few as 100 viable trophozoites as determined by ethidium bromide staining, while no signal was obtained from 10(6) trophozoites killed by heat, desiccation, or UV radiation. This assay was also capable of distinguishing P. carinii from other common fungi present in the air. Therefore, this molecular viability assay may be useful in conjunction with standard bioaerosol collection devices and procedures for the detection of viable P. carinii collected from various indoor environments. It may also be useful in confirming the presence of viable trophozoites in respiratory specimens collected by noninvasive techniques from putatively infected individuals.